Association between Paravertebral Block and Pain Score at the Time of Hospital Discharge in Oncoplastic Breast Surgery: A Retrospective Cohort Study. Issue 6 (10th May 2021) - Buzney, Catherine D.; Lin, Liz Z.; Chatterjee, Abhishek; Gallagher, Sean W.; Quraishi, Sadeq A.; Drzymalski, Dan M.
Abstract : Background: Using nonopioid analgesics may decrease the risk of patients chronically using opioids postoperatively. The authors evaluated the relationship between paravertebral block and pain score at the time of hospital discharge. Methods: The authors performed a retrospective cohort study of 89 women with American Society of Anesthesiologists Physical Status I to III undergoing oncoplastic breast surgery with 20 to 50 percent breast tissue removal and immediate contralateral reconstruction between August of 2015 and August of 2018. The primary outcome was pain score at hospital discharge with or without paravertebral block. The secondary outcome was postoperative length of stay. Data were analyzed using the Wilcoxon rank sum test, t test, Fisher's exact test, univariable and multivariable regression, Kaplan-Meier analyses, and Cox regression. Results: Median pain score at hospital discharge was lower with paravertebral block [2 (interquartile range, 0 to 2) compared to 4 (interquartile range, 3 to 5); p < 0.001]. Multivariable regression revealed that pain score at the time of hospital discharge was inversely associated with paravertebral block after adjusting for age, body mass index, American Society of Anesthesiologists class, extent of lymph node surgery, and duration of surgery ( p < 0.001). Pain score at hospital discharge was also associated with total opioid consumption during the first 24 hours after surgery ( p = 0.001). Patients who received paravertebral blocks had median total 24-hour postoperative opioid consumption in morphine equivalents of 7 mg (interquartile range, 3 to 10 mg) compared with 13 mg (interquartile range, 7 to 18 mg) ( p < 0.001), and median length of stay of 18 hours (interquartile range, 16 to 20 hours) compared with 22 hours (interquartile range, 21 to 27 hours) ( p < 0.001). Conclusion: Paravertebral blocks are associated with decreased pain score at the time of hospital discharge. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.